Does Society Influence the Gender Gap in Risk Attitudes? Evidence from East and West Germany - Cornelia Chadi; Uwe Jirjahn (Global Labor Organization (GLO), 2019)
Previous international research has shown that women are more risk averse than men. This gives rise to the question whether the gender gap in risk attitudes is shaped by the social environment. We address this question by examining risk attitudes among East and West Germans. Originated from different family policies during Germany's separation, East Germans have more equal gender roles than West Germans. Thus, if the gender gap reflects socially constructed norms, it should be smaller among East Germans. Using data of the German Socio-Economic Panel (SOEP), our empirical analysis confirms this prediction. Specifically with respect to career and financial matters, the gender gap in risk tolerance is smaller among East Germans. We find no evidence that the East German gender gap has converged to the higher West German level after reunification. By contrast, the West German gap has narrowed over time.
Keywords: D91; J16; P51; 330; Risk Preferences; Gender Roles; Nurture; Family Policy